Cooperative DNA binding mediated by KicGAS/ORF52 oligomerization allows inhibition of DNA-induced phase separation and activation of cGAS. Issue 16 (13th August 2021) - Bhowmik, Debipreeta; Du, Mingjian; Tian, Yuan; Ma, Siming; Wu, Jianjun; Chen, Zhijian; Yin, Qian; Zhu, Fanxiu
Abstract: Cyclic GMP-AMP synthase (cGAS) is a key DNA sensor that detects aberrant cytosolic DNA arising from pathogen invasions or genotoxic stresses. Upon binding to DNA, cGAS is activated and catalyzes the synthesis of cyclic GMP-AMP (cGAMP), which induces potent antimicrobial and antitumor responses. Kaposi sarcoma-associated herpesvirus (KSHV) is a human DNA tumor virus that causes Kaposi sarcoma and several other malignancies. We previously reported that K SHV i nhibitor of cGAS (KicGAS) encoded by ORF52, inhibits cGAS enzymatic activity, but the underlying mechanisms remained unclear. To define the inhibitory mechanisms, here we performed in-depth biochemical and functional characterizations of KicGAS, and mapped its functional domains. We found KicGAS self-oligomerizes and binds to double stranded DNA cooperatively. This self-oligomerization is essential for its DNA binding and cGAS inhibition. Interestingly, KicGAS forms liquid droplets upon binding to DNA, which requires collective multivalent interactions with DNA mediated by both structured and disordered domains coordinated through the self-oligomerization of KicGAS. We also observed that KicGAS inhibits the DNA-induced phase separation and activation of cGAS. Our findings reveal a novel mechanism by which DNA viruses target the host protein phase separation for suppression of the host sensing of viral nucleic acids. Graphical Abstract: